Predictive factors and pattern of central lymph node metastasis in unilateral papillary thyroid carcinoma. Issue 1 (February 2016) - Ji, Yong Bae; Yoo, Han Seok; Song, Chang Myeon; Park, Chul Won; Lee, Chang Beom; Tae, Kyung
Abstract: Objective: Prophylactic central neck dissection (CND) for papillary thyroid carcinoma (PTC) remains controversial. The aim of this study was to evaluate the patterns and predictive factors of central lymph node metastasis in cases of PTC that were clinically determined to be node negative. Methods: We studied 485 patients who have unilateral PTC without clinical lymph node metastasis and underwent total thyroidectomy and prophylactic bilateral CND from 2003 to 2012, retrospectively. The frequency, subsite and predictive factors of central lymph node metastasis were analyzed. Results: In total, 166 (32.4%) patients had occult central lymph node metastases. The most common subsite of central node metastases was the ipsilateral paratracheal lymph node (26.0%), followed by pretracheal (12.5%), prelaryngeal (5.0%), and contralateral paratracheal (3.9%) lymph nodes. The tumor size larger than 0.5 cm ( p = 0.003), age under 45 ( p < 0.001) and extrathyroidal extension ( p = 0.028) were associated with ipsilateral central compartment metastasis in multivariate analysis. Contralateral central node metastasis was associated with tumor size >3 cm, age under 45, and multifocality and ipsilateral central node metastasis in univariate analysis, but it was associated with only ipsilateral central node metastasis in multivariate analysis ( p = 0.001). Conclusion: Prophylactic CND might be considered for PTC patients with large tumor size or extrathyroidal extension based on rates of lymph node metastasis. Unilateral CND might be appropriate as prophylactic CND due to the low metastatic rate to the contralateral paratracheal node.